Focus sur les expertises d'articles soumis, portant sur des dispositifs de formation médiatisée - Elke Nissen (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This study analyses reviews made by members of two different scientific committees on submitted papers, dealing with technology-enhanced learning design. It aims at identifying major difficulties authors encounter in this type of research and publication. These difficulties are related, on the one hand, to writing issues such as the necessary balance between description of the learning design and research, and text "alignment" (concept based on Biggs 1996, Biggs & Tang 2011)–or text coherence. On the other hand, they are related to research aspects. They concern, for instance, the authors' positioning as teachers or as researchers, or the delimitation of their research question.